Biodiversity and health : linking life, ecosystems and societies - Morand, S.; Lajaunie, Claire (Biodiversity and health., 2018)
"Biodiversity and Health: Linking Life, Ecosystems and Societies fills the gap between the ecology of health and the concepts supported by international organizations, such as EcoHealth and One Health. The book provides a unique opportunity to demonstrate how ecological sciences, environmental sciences, medical sciences, and social sciences may contribute to improve human health through conserving biodiversity and the services it provides to societies. Presents the first book to give a broad and integrated overview of the scientific disciplines that contribute to health. From evolutionary ecology, to laws and policies, this book explores the links between health and biodiversity. Demonstrates how ecological sciences, environmental sciences, medical sciences, and social sciences may contribute to improve human health"--